Paeonia officinalis for Acute Anal Fissure: A Prospective, Single-Group, Open-Label, Pre–Post Comparison Study - Dixit, Ashish Kumar; Yadav, Moorat Singh; Javed, Danish; Tarique, Barkati Md (Homeopathy, 2025)
Acute anal fissure (AF) causes significant pain and discomfort, sometimes requiring invasive treatment. This study evaluates the usefulness and safety of homeopathic Paeonia officinalis mother tincture (Q) in the management of acute AF.An open-label, prospective, pre–post comparison cohort study was conducted on 34 participants diagnosed with acute AF. Paeonia officinalis Q was administered orally (10 drops in 50 mL of water, once daily) for 12 weeks alongside supportive care that included dietary advice. Outcome measures were: pain intensity assessed using a Visual Analog Scale (VAS; range: 0–10); level of strain during defecation using the Defecation Strain Score (DSS); Outcome Related to Impact on Daily Living (ORIDL) score for main complaint and overall well-being; and degree of healing of fissure (HoF) by visual clinical examination.VAS score reduced significantly from baseline (8.94 ± 0.81) at 12 weeks (0.11 ± 0.32), with a mean decrease of 8.82 ± 0.13 (p < 0.001), while DSS decreased from a median of 3 to 0 (change, 3; inter-quartile range [IQR], 2–3; p < 0.001). ORIDL scores for main complaint increased from 2 to 4 (change, 1; IQR, 1–2) and well-being from 3 to 4 (change, 1; IQR, 1–1; p < 0.001). By 12 weeks, fissures healed completely in 30 (88.2%) participants, with no serious adverse events reported.Homeopathic Paeonia officinalis Q, combined with concomitant care advice, appears useful in reducing pain and straining while promoting fissure healing in acute AF patients. The potential influence of confounders limits attribution of positive outcomes to the homeopathic intervention alone.
Keywords: anal fissure; healing; homeopathy; paeonia officinalis